ADMINISTRATION OF LEARNING MANAGEMENT CONDUCIVE TO EARLY CHILDHOOD EXECUTIVE FUNCTION OF SCHOOL ADMINISTRATORS UNDER LAMPANG PRIMARY EDUCATION SERVICE AREA OFFICE 3 - Tanaima, Nurumol; Thienpraphaku, Panatanon (Academic Journal Phranakhon Rajabhat University, 2024)
The objective of this research was to study the condition and management guidelines of learning management conducive to early childhood executive function of school administrators under Lampang Primary Educational Service Area Office 3. The population consisted of 44 school administrators and 56 preschool teachers. The tools included a 5-point rating scale questionnaire regarding learning management conducive to early childhood executive function of school administrators under Lampang Primary Education Service Area Office 3, and group discussion recording forms. Data analysis employed basic statistics such as percentage, mean, standard deviation, and content analysis. The research findings indicated that: 1) the management condition conductive to early childhood executive function of school administrators was overall at a high level. The leadership had the highest average, followed by planning, organization, and control, respectively, and 2) there were a total of 22 management guidelines conducive to early childhood executive function of school administrators. These included 5 guidelines for planning, 6 guidelines for organization, 6 guidelines for leadership, and 5 guidelines for control.